A solar fiber daylighting system without tracking component. (December 2019) - He, Kaiyan; Chen, Ziqian; Zhong, Shiuku; Qian, Yingda; Liu, Haoyue; Yin, Junhua; Zhou, Bangdi
Highlights: A transparent solid concentrator is designed. A fixed optical fiber daylighting system is proposed. AN optical fiber daylighting system could need no tracking component. Abstract: A fixed optical fiber solar system for long distance daylighting used in buildings is proposed. Its structure and working principle have been introduced. The proposed system takes the advantages of both light pipe and traditional optical fiber system and overcomes their shortcomings. The receiving surface of the new system is like a spherical sunflower. It has a simple structure, good integrity, flexible light transmission and light redistribution characteristics. Especially, it does not require a tracking device. Both the theoretical analysis and field test have proved that the system has the same reception feature as the traditional optical fiber system with a tracking device. Its graph of the illuminance roughly follows the fluctuation of the curve of the solar irradiance. A small test system with a solar receiving area of 1.69 × 10 −2  m 2 and receiving angle of 32° was made to verify the feasibility of the fixed optical fiber system. Experimental result had proved that the proposed system is feasible. On average, the output illuminance inside a small test room is up to about 180 lx in a distance of 0.4 m from the bundled end of the fibers with the solar irradiance being about 600 W/m 2, approximately 300 lx under approximately 800 W/m 2 . The simple structure, expectable low cost, almost maintenance-free and a predictable long life of the new system will facilitate the mass production and the viable commercialization of daylighting systems.